2020
DOI: 10.33945/sami/ajca.2020.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation to Corrosion Inhibition Efficiency of Some Chloroquine Derivatives Using Density Functional Theory

Abstract: In this work, the potential of corrosion inhibition of four chloroquine derivatives; N 4-(7-Chloroquinolin-8-ol-4-yl)-N 1 ,N 1-diethylpentane-1,4 diamine (M2), N 4-(7-Chloroquinolin-8-amino-4-yl)-N 1 ,N 1-diethylpentane-1,4 diamine (M3) and N 4-(5-bromo-7-Chloroquinolin-8-amino-4-yl)-N 1 ,N 1-diethylpentane-1,4-diamine (M4) were investigated. Their chemical descriptors which include molecular volume, softness, chemical hardness, electronegativity, fraction (ΔN) and electrophilicity index (ω) dipole moments, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…On the other hand, TADH has the lowest E LUMO values, associated with the highest tendency to accept electrons from the metal ion. The reduced E LUMO values suggested increased CI adsorption on the metal surface, which improved the inhibition efficiency. , Overall, the study found that the value of E LUMO decreased in the following order: CBH > SDH > GADH > MADH > AADH > ODH > TADH.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…On the other hand, TADH has the lowest E LUMO values, associated with the highest tendency to accept electrons from the metal ion. The reduced E LUMO values suggested increased CI adsorption on the metal surface, which improved the inhibition efficiency. , Overall, the study found that the value of E LUMO decreased in the following order: CBH > SDH > GADH > MADH > AADH > ODH > TADH.…”
Section: Resultsmentioning
confidence: 77%
“…The reduced E LUMO values suggested increased CI adsorption on the metal surface, which improved the inhibition efficiency. 14,17 Overall, the study found that the value of E LUMO decreased in the following order: CBH > SDH > GADH > MADH > AADH > ODH > TADH.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The dipole moment (DM) is the first derivative of the energy with respect to an applied field [36] electronic parameter resulting from the unequal distribution of charges on various atoms in a molecule. It measures the polarity of a polar covalent bond, predicts the direction of the corrosion inhibition process, and gives information about the distribution of electrons in the molecules [36][37][38]. The total dipole moment, on the other hand, simply represents a molecule's global polarity.…”
Section: Quantum Descriptors Of Inhibitorsmentioning
confidence: 99%
“…The ΔN values shown in Table 1 follow the order: B5 > B3 > B4 = B6 > B2 > B1 > A6 > A4 > A2 > A3 > A5 > A1. Negative values of ΔEback−donation displayed by all molecules indicate that charge transfer between the surface of the metals and the molecules is energetically favored, implying that all molecules can make electrons available via back-donation [35].…”
Section: Corrosion Inhibition Frontier Orbital Energies and Reactivit...mentioning
confidence: 99%